2019
DOI: 10.1016/j.nepr.2019.102641
|View full text |Cite
|
Sign up to set email alerts
|

Midwives transition to practice: Expectations and experiences

Abstract: The Rural Private Midwifery Education Program (RPMEP), a 2013 strategic response to midwifery workforce issues by the Queensland Government was unique in the Australian context. Midwifery students were embedded within a private midwifery caseload practice or rural publicly funded midwifery group practice (MGP). Continuity of midwifery care was at the core of the students' learning experience. This paper describes a study designed to explore the expectations and experiences of this group of newly qualified midw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 26 publications
0
17
0
Order By: Relevance
“…The impact of losing the relationship with women paradoxically demonstrated to students the benefits of continuity of care experiences. The essential CCE component of Australian midwifery courses, highly valued by students ( Sidebotham, 2014 ; Tierney et al, 2017 ), provides much appreciated authentic learning experiences and a woman-centred philosophy of midwifery care ( Kuliukas et al, 2020 ) in preparation for post-graduation practice ( Griffiths et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…The impact of losing the relationship with women paradoxically demonstrated to students the benefits of continuity of care experiences. The essential CCE component of Australian midwifery courses, highly valued by students ( Sidebotham, 2014 ; Tierney et al, 2017 ), provides much appreciated authentic learning experiences and a woman-centred philosophy of midwifery care ( Kuliukas et al, 2020 ) in preparation for post-graduation practice ( Griffiths et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…This was because graduates felt unwelcomed leading to a feeling of unworthiness and low self-esteem, which negatively affected their confidence. Griffiths et al (2019) shared the same sentiments when they reported that newly qualified midwives experienced rejection and isolation as they were ignored when seeking help, which caused distress especially in front of the patients and graduates interpreted the behaviour as being disrespectful (Javanmard et al 2019;Kensington et al 2016). Provision of positive support by experienced midwives made newly qualified midwives to feel valued when treated positively as part of the team and having responsibility for practice, which contributed greatly to learning and boosted their confidence, thus, improving their performance (Bradshaw, Tighe & Doody 2018;Simane-Netshisaulu & Maputle 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Newly graduated midwives experienced physical responses to transition shock, which were presented with somatic complaints such as headaches (Odland, Sneltvedt & Sörlie 2014;Reynolds, Cluett & Le-May 2014). Midwifery graduates were overwhelmed and felt inadequate as they were not accepted as part of the team and, therefore, denied the opportunity to learn, which negatively affected their competence and confidence level predisposing them to vulnerability (Black 2018;Griffiths et al 2019). The reason why newly qualified midwives are placed in the state healthcare facilities is that they should receive the necessary assistance from experienced and qualified midwives, which may enable them to effectively progress from being students to becoming qualified midwives who are autonomous, competent and effective professionals capable of provision of quality midwifery care.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, coherent program values based firmly on a midwifery philosophy will facilitate the development of resourcefulness, capability, sense of purpose and a strong midwifery philosophy which can transcend culture and context of practice 45,46 . This will facilitate confidence and competence in student midwives when they are faced with situations they find professionally or clinically challenging.…”
Section: Curriculum Coherencementioning
confidence: 99%